The Frequency of Incidental Findings in Prostate Multiparametric Magnetic Resonance Imaging - Salbas, Ali; Bayir, Atakan; Gumus, Cesur (The European Research Journal, 2026)
Objectives: This study aimed to evaluate the prevalence, distribution, and clinical significance of incidental findings on multiparametric magnetic resonance imaging (mpMRI) performed for suspected prostate cancer, and to assess differences based on patient age. Methods: This retrospective study reviewed the mpMRI examinations of 532 patients. Incidental findings were identified and categorized as genitourinary or extragenitourinary, and further classified as clinically significant or non-significant. The prevalence and characteristics of incidental findings were analyzed and compared between two age groups (≤65 and >65 years). Results: Of the 532 patients, 243 (45.7%) had at least one incidental finding, for a total of 275 findings. The majority (94.9%) were clinically non-significant, with bladder wall thickening (n=58) and fat-containing inguinal hernias (n=40) being the most common. Fourteen findings (5.1%) were deemed clinically significant, including bladder carcinoma (n=3), iliac artery aneurysm (n=2), and rectal cancer (n=1). The prevalence of incidental findings was significantly higher in patients aged >65 years compared to those ≤65 years (51.6% vs. 37.2%, P=0.001), although there was no significant difference in the rate of clinically significant findings between the age groups (P=0.128). Conclusions: Incidental findings are frequently detected in prostate mpMRI, occurring in nearly half of patients. Although most are benign, a small but important proportion (5.1%) are clinically significant and may impact patient management. These results underscore the necessity for radiologists to perform a comprehensive evaluation of the entire imaging field of view.